S44 Repair of acute respiratory distress syndrome in COVID-19 by stromal cells (REALIST-COVID trial): 1 year follow up for safety and pulmonary dysfunction. (11th November 2022) - Gardiner, HJ; Gorman, EA; Rostron, AJ; Shankar-Hari, M; Bannard-Smith, J; Bentley, AM; Brealey, D; Campbell, C; Curley, G; Clarke, M; Dushianthan, A; Hopkins, P; et al.
Abstract : Introduction and Objectives: REALIST-COVID was a UK multicentre, double-blind randomised, allocation concealed, placebo-controlled phase 2 trial, investigating a novel mesenchymal stromal cell (MSC) product (ORBCEL-C cryopreserved, allogeneic, umbilical cord-derived CD362 enriched MSCs) in patients with ARDS due to COVID-19. Here we report follow up of the REALIST-COVID cohort at 1 year, with the aim of further evaluation of ORBCEL-C MSC safety. Methods: 1-year mortality status was recorded from GP and hospital records where possible. Survivors at 1 year were followed up for significant medical events (SMEs) via telephone interview, medical record review, or contact with GP. Interstitial lung disease (ILD) and pulmonary dysfunction on clinically indicated thoracic computerised tomography (CT) and pulmonary function tests (PFTs) was recorded. Results: Mortality at 1-year was 29% (n=8/28) in the ORBCEL-C group and 28% (n=8/29) in the placebo group. One patient in the ORBCEL-C group died between day 90 and 1 year. 41 survivors were followed up at 1 year (20 in ORBCEL-C, 21 in placebo). Significant medical events in survivors were similar in both groups (7 events in 6 patients in the ORBCEL-C group and 11 events in 9 patients in the placebo group). Classification of SMEs is summarised in table 1 . Thoracic CTs were available for 12 participants (ORBCEL-C n=5/20, placebo n=8/21). Median time to CT and results are summarised in table 1 ). Evidence of ILD was similar in each group. PFTs were available for 18 participants (ORBCEL-C n=10/20, placebo n=8/21). Median time to PFTs and results are summarised in table 1 . FEV1, FVC, FEV1/FVC ratio and TLCO were similar between groups. There was a high rate of impairment of transfer factor (TLCO<80% predicted) in participants from both groups. Conclusions: One year follow up supports the safety of ORBCEL-C MSCs in patients with moderate to severe ARDS due to COVID-19. A similar incidence of pulmonary dysfunction is reported in both groups at long term follow up. Please refer to page A?? for declarations of interest related to this abstract.